Positive size and scale effects of all-cellulose composite laminates. (June 2016) - Dormanns, Jan W.; Weiler, Felix; Schuermann, Jeremias; Müssig, Jörg; Duchemin, Benoît J.C.; Staiger, Mark P.
Abstract: Negative size effects are commonly reported for advanced composite materials where the strength of the material decreases with increasing volume of the test specimen. In this work, the effect of increasing specimen volume on the mechanical properties of all-cellulose composites is examined by varying the laminate thickness. A positive size effect is observed in all-cellulose composite laminates as demonstrated by a 32.8% increase in tensile strength as the laminate thickness is increased by 7 times. The damage evolution in all-cellulose composite laminates was examined as a function of the tensile strain. Enhanced damage tolerance concomitant with increasing specimen volume is associated with damage accumulation due to transverse cracking and strain delocalisation. A transition from low-strain failure to tough and high-strain failure is observed as the laminate thickness is increased. Simultaneously, scale effects lead to an increase in the void content and cellulose crystallinity at the core, with increasing laminate thickness.